REFLECTION OF ALCOHOLISM IN THE LYRICS “CHANDELIER” BY SIA - Rahmah, Tsaqila Idzhan Nur; Hikmat, Mahi M. (Universitas Putera Batam, 2024)
This research aims to determine the author's psychology in creating a literary work through a psychoanalytic perspective. The creation of a lyric cannot be separated from its author. Sia Kate Isobelle Furler and Jesse Shatkin wrote the lyrics to the song entitled Chandelier. This research was conducted to find out how the psychological role of the author influences the literary work created by the author. The psychological theory that is very dominant in the analysis of literary works is Freud’s theory, where this theory differentiates personality into three types, namely Id, Ego, and Super Ego. Data collection uses documentation techniques from primary data sources, namely the lyrics of the song “Chandelier” and secondary data sources in the form of books, research journals, and articles which relevant. This research uses qualitative descriptive methods to conduct an analysis, using library research methods and content analysis methods to collect and analyze the data used. The research results show that the lyrics she created reflect the psychological state of the author. Represented through several sentences and characters built into the lyrics, which consist of 3 aspects of the Id, 3 aspects of the ego, and 1 aspect of the superego. This results in the conclusion that the psychological condition of the writer, Furler, who is a former alcoholic, can influence the creation of the lyrics of the song Chandelier where alcohol acts as an escape from the pain she felt, this is in line with Sigmund Freud’s psychoanalytic theory.